IMPLEMENTASI KONTEN MARKETING SOSIAL MEDIA INSTAGRAM PMJ UNIFORM TAHUN 2024 - Muhammad Miftahul Huda; Widya Sastika (JURNAL LENTERA BISNIS, 2024)
Fashion has always been a necessity for everyone from babies to adults. Every Indonesian knows what they wear every day. Globally, fashion means a popular style in a particular culture to support the appearance of someone who uses it, or it can be interpreted as a unique characteristic for the person who wears it. The purpose of this study was to determine methods for implementing, executing, and evaluating business social media marketing content for PMJ UNIFORM marketing. Data was collected through observations of other uniform competitors on Instagram social media and interviews with internal MSME informants. This research  was conducted  using  descriptive  qualitative  research,  with  object analysis. The results of this study found marketing content needed to increase interaction and knowledge on the @pmjuniform_official Instagram account, when this research was conducted PMJ UNIFORM did not have an Instagram account as a means of promotional media on the internet. With that, the hope of the researcher is also umkm will continue to post interesting and consistent content after this research, because it is very important to maintain and increase insight on Instagram in order to increase sales.